Incorporating Powtoon as a learning activity into a course on technological innovations as didactic resources for pedagogy programs - Rioseco, Marcelo (2017)
This paper describes the incorporation of the PowToon program as an activity for a course on Technological Innovations as Didactic Resources,in two pedagogy programs at Universidad Catolica del Maule (UCM) in Chile. This activity has been designed based on the ‘learning by doing’ paradigm, backed up by existing resources available in The cloud. The students’ perceptions about the use of the program were collected through the use a closedended/open-ended question survey. The data analysis was carried out by using a mixed methodology (qualitative/quantitative) and, in general terms, showed positive results on the use of PowToon, not only on the motivational aspect, but also regarding its contribution on learning new contents and developing ICTrelated abilities. However, opinions are still divided on the aspect of userfriendliness.